Basel III new liquidity framework and Malaysian commercial banks profitability - Rasidah Mohd Said (Penerbit Universiti Kebangsaan Malaysia, 2018)
In the light of the 2007-2008 global financial crisis, Basel Committee on Banking Supervision proposed the Net Stable Funding Ratio (NSFR), a new liquidity framework under Basel III. Its aim is to promote sustainable funding structures of the financial institutions. This current paper attempts to analyse NSFR impact on Malaysian commercial banks profitability. Using panel data of eight domestic Malaysian commercial banks for the period 2005-2011, the results suggest there is a convincing evidence that this new liquidity ratio is an important factor in affecting the sample banks’ profitability. The ability of banks in managing the stability of their funding sources as well as liquidity of its asset is an advantage to them and is translated into higher profitability. In addition, this study also confirms finding of previous studies that relates bank-specific determinants and profitability.